Tunable Magnetic Fano Resonances on Au Nanosphere Dimer–Dielectric–Gold Film Sandwiched Structure - Gong, Tianxun; Guan, Fang; Wei, Zhenjiang; Huang, Wen; Zhang, Xiaosheng (Frontiers in Physics, 2021)
The Fano resonance demonstrates excellent performance due to its narrow asymmetrical spectral line shape, and its sensitivity to structure and material parameters changes. Compare to conventional Fano resonances, the Fano resonance generated by the magnetic dipole is more advantageous in terms of high absorption and low loss. In this paper, we proposed an Au nanosphere dimer-dielectric-gold film sandwiched structure that supports the magnetic Fano resonance mode. And the Fano resonance can be tuned efficiently from visible to near infrared wavelength by changing the size of the gold nanospheres and the thickness of the dielectric layer. Different from the single gold nanosphere-dielectric-film structure, the results suggest that the proposed structure is sensitive to the polarization direction of the excitation light. Based on the above characteristics, the proposed structure can be applied in multi-band sensing, surface enhanced Raman spectroscopy and dynamically adjustable optical switches.